Cu-alginate hydrogels in microfluidic systems: a sustainable catalytic approach for click chemistry - Ramšak, Arijana; Gazvoda, Martin; Plazl, Igor; Ambrožič, Rok (Frontiers in Chemical Engineering, 2024)
This work explores the innovative use of copper-alginate (Cu-alginate) hydrogels within microfluidic systems to catalyze dipolar cycloaddition reactions, emphasizing green chemistry principles and process intensification. Utilizing naturally occurring biopolymers, such as alginates, provides an environmentally friendly alternative to conventional catalyst supports due to their biocompatibility, biodegradability, and effective metal ion immobilization capabilities. The integration of these biopolymer-based catalysts into microfluidic devices allows for precise control over reaction conditions, leading to enhanced reaction kinetics and mass transfer efficiencies. Our results demonstrate that Cu-alginate hydrogels effectively catalyze the formation of 1,4-disubstituted 1,2,3triazoles through [3+2] dipolar cycloaddition reactions with high regioselectivity and conversion. The microfluidic setup ensures rapid and efficient synthesis, surpassing traditional batch reaction methods in both reaction rate and environmental impact by reducing solvent usage and waste generation. Furthermore, the use of microfluidics contributes to the reproducibility and scalability of the synthesis process, important for industrial applications. The model-based design and its simulations have been employed to further understand and optimize the reaction system. Diffusion through the gel layer and catalytic reaction kinetics estimated from experimental data were included in the model, providing a theoretical foundation for a comprehensive process evaluation. This study not only advances the field of sustainable catalysis by demonstrating the practical utility of biopolymer-supported catalysts in microfluidic systems, but also sets the stage for further research into biopolymer applications in complex chemical syntheses.